IMPLEMENTASI PERATURAN DAERAH KOTA SEMARANG NOMOR 11 TAHUN 2000 TERHADAP PENGATURAN DAN PEMBINAAN PEDAGANG KAKI LIMA (Studi Pada Satuan Polisi Pamong Praja Kota Semarang) - La Pomaasaa Pomaasaa; Gunarto Gunarto (UNISSULA Semarang, 2018)
Implementation of Regional Regulation of Semarang City Number 11 Year 2000 Against Arranging and Fostering of Street Traders In Semarang City conducted by Satuan Polisi Pamong Praja there are some cases which one of them is: Order of street vendors (PKL) who build permanent building that supposed the building can Dismantled pairs as listed in the Regional Regulation of Semarang City No. 11 of 2000 in Chapter V Article 8.The type of research used in this research is sociological legal research supported by empirical juridical. In relation to the type of research conducted is a sociological legal research because it departs from the existence of the gap in the principle / legal norms are blurred and void norms in the arrangement of street vendors in the city of Semarang.The results showed that in implementing the Local Regulation of City of Semarang Number 11 Year 2000 on the Arrangement and Fostering of Street Traders in Semarang City, the Pamong Praja Police Unit always use the method of arrangement by always trying to dialogue with Street Traders to find the best solution between the Police Unit Pamong Praja with a Street Trader to reach a mutual agreement. The collective agreement was made in order to avoid rejection at the time of the curbing which could result in clash between the Civil Service Police Unit and the street vendors which could result in both losses.Keywords : Implementation, Local Regulation, Arrangement and Guidance, Street Traders.